Total arterial myocardial revascularization in octogenarians - Kędziora, Anna; Konstanty-Kalandyk, Janusz; Litwinowicz, Radosław; Mazur, Piotr; Guzik, Bartłomiej; Bryniarski, Krzysztof; Piątek, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
According to the current ESC/EACTS Myocardial Revascularization Guidelines, the left internal mammary artery (LIMA) should always be implanted to graft the left anterior descending (LAD) artery, but an additional arterial graft should be considered in appropriate patients undergoing coronary artery bypass grafting (CABG) [1]. In spite of inconclusive 10-year results from the Arterial Revascularization Trial (ART) [2], observational studies underline the superior patency of arterial grafts [3]. Nevertheless, based on the data published by the Society of Thoracic Surgeons (STS), bilateral internal mammary grafts are implanted in as few as 5% of CABG cases, and the use of the radial artery (RA) has declined by approximately 33% within the last decade [4].